2016
DOI: 10.1007/s00167-016-4309-5
|View full text |Cite
|
Sign up to set email alerts
|

Microbial resistance related to antibiotic-loaded bone cement: a historical review

Abstract: The literature for and against a link between ALBC and the development of microbiological resistance is reviewed and presented. It is concluded that further research is needed to develop a defined set of indications for the use of ALBC in the management of periprosthetic joint infection. In addition, further research into alternative antimicrobial therapies in this area should be encouraged.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…Second, we excluded patients who were treated with antibiotics other than anti-MRSA drugs or aminoglycosides, which are the most common antibiotics used with bone cement. 24 Diagnosis of periprosthetic joint infection remains challenging, even though a wide variety of tests and combinations of tests are used for diagnosis. Nevertheless, the database used in this study did not include information, such as the results of serum markers or culture of periprosthetic fluid.…”
Section: Discussionmentioning
confidence: 99%
“…Second, we excluded patients who were treated with antibiotics other than anti-MRSA drugs or aminoglycosides, which are the most common antibiotics used with bone cement. 24 Diagnosis of periprosthetic joint infection remains challenging, even though a wide variety of tests and combinations of tests are used for diagnosis. Nevertheless, the database used in this study did not include information, such as the results of serum markers or culture of periprosthetic fluid.…”
Section: Discussionmentioning
confidence: 99%
“…ALBC has been widely used for the treatment of infected arthroplasty, and given the increased incidence of this type of infection, a large number of review papers is found in which aspects such as release mechanisms, clinical efficacy, and safety of the ALBC are discussed [13,118,[129][130][131][132][133].…”
Section: Antimicrobial Properties In Acrylic Bone Cementsmentioning
confidence: 99%
“…PMMA is incompatible with temperature-sensitive antimicrobials due to heat released during polymerization and requires explantation [7]. Unless removed in a timely manner, antimicrobials are eluted at subtherapeutic dosages that may promote antimicrobial resistance [10]. CaSO 4 is a resorbable biomaterial that eliminates the need for removal surgeries.…”
Section: Introductionmentioning
confidence: 99%